Qualitative Research on the Viewpoints of Parents Regarding Active Games Played by the Children Aged Between 4-5 - Baydar, Hacer Ozge; Tingaz, Emre Ozan; Hazar, Muhsin; Hazar, Kurset; Gokyurek, Belgin (European Scientific Journal, ESJ, 2017)
The purpose of this study is to examine the viewpoints of parents on their 4-5-year-old children who were playing active games. The parents had expressed that active games have positive influences on the cognitive development of children. Also, it has a significant influence on the decisionmaking process and focusing in general. Majority of the parents stated that active games have positive influences on the emotional development of their children in general terms. They expressed this with the term â€œbeing happyâ€ and â€œbeing able to express oneselfâ€. The parents, who thought that active games have negative influences on the emotional development of their children, expressed this as â€œbeing angryâ€. On the other hand, the parents also thought that active games contribute greatly to the psychomotor development of their children. Thus, they expressed this as â€œpositive influences on physical development of their childrenâ€. As the last item, the parents considered active games to have positive contributions to the social development of their children. They, however, expressed this thought with expressions like â€œbeing social, establishing communications, learning sharing, etc.â€. In conclusion, it has been observed that the viewpoints of the parents on active games were generally positive in terms of cognitive, emotional, and social and psychomotor development areas.